The dark side of online home-schooling after Covid-19 in Sri Lanka - Mohamed Yaseen Minnathul Suheera; Thaseem Mohamed Fathima Wazeema (SIMULACRA: JURNAL SOSIOLOGI, 2022)
Free education has been particularly influential in the educational upliftment of poor families in Sri Lanka. However, over the past year and a half, similar to all other countries in the world, the educational conditions of Sri Lanka have also been affected by the unexpected circumstances of Covid-19 pandemic. However, the Sri Lankan government has taken various initiatives to ensure the educational activities. In this regard, this study aims to determine the impacts of current home-based educational activities on low-income families in Sri Lanka. Qualitative research method was used in this study, 90 low-income families were selected as the study sample. In-depth interview technique and observation were used to collect data and thematic analysis method was used for data analysis. As a result of this study, most of the students from low-income families are unable to engage in the online learning process at home, learning activities of children have become a burden to the parents and parents temporarily abstain their children from learning in some families. Therefore, the study recommends that the government should concentrate to facilitate the children in such low-income families to continue their learning in a non-burden and cost-efficiency manner during the pandemic situations.